Bio-bibliometric Study of Gali Madhavi Latha, A Pioneering Female Geotechnical Engineer behind the World’s Highest Railway Bridge at Chenab - Koley, Susanta (Journal of Data Science, Informetrics, and Citation Studies)
This study aims to evaluate the scholarly impact of Dr. Gali Madhavi Latha, a prominent Indian female geotechnical engineer, through a technometric and bibliometric assessment. The objectives are to quantify her research productivity, collaboration patterns, and influence on geotechnical engineering. Publication data spanning 1998-2025 were sourced from Google Scholar and ResearchGate, validated, and analysed using standard scientometric indicators. The dataset comprises 200 publications, including 12 single-authored and 188 co-authored, with journal articles representing 56% of her output. A significant concentration of her work appears in Geotextiles and Geomembranes, Indian Geotechnical Journal, and International Journal of Geosynthetics and Ground Engineering (together 40 papers). Peak productivity occurred between 2022 and 2025, averaging 7.14 papers per year, with a Productivity Coefficient of 0.68. She has collaborated extensively with T.G. Sitharam (23 joint publications). Her most cited work (1999) has 431 citations. Key metrics, including DC (0.94), CC (2.32), and MCC (0.47), highlight her collaborative and scholarly influence. Validation of Lotka’s and Bradford’s laws further contextualizes her contributions. This study demonstrates Dr. Latha’s sustained, high-impact research, bridging experimental, analytical, and applied geotechnical engineering, underscoring her prominence in both academic and practical engineering domains.
Keywords: Best Woman Geotechnical Researcher; Bibliometric; Chenab Railway Arch Bridge; Design-as-you-go method; Gali Madhavi Latha; Geotechnical engineering; Indian Institute of Science (IISc) Bangalore; Kashmir valley; Women geotechnical engineer; World’s highest rail bridge.